Investigating Rhetorical Strategies Based on the Andersen Model in a Single Corpus of Concession (Defeat) Speeches - fathor rahman (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
This study investigates the rhetorical strategies employed by Agus Harimurti Yudhoyono (AHY) in his concession speech following the 2017 Jakarta gubernatorial election. The research focuses specifically on AHY’s political rhetoric as a form of strategic communication used to construct political legitimacy, maintain public credibility, and shape post-electoral public perception after defeat. Using a qualitative approach within a constructivist paradigm, this study applies Andersen’s Model of Political Rhetoric as the primary analytical framework, complemented by Aristotelian rhetorical concepts to interpret persuasive dimensions within the speech. The unit of analysis consists of rhetorical segments, sentence structures, and symbolic expressions contained in AHY’s concession speech broadcast by CNN Indonesia on 15 February 2017. Data were collected through document analysis and analyzed using open, axial, and selective coding to identify recurring rhetorical patterns and thematic categories. The findings demonstrate that AHY’s concession rhetoric emphasizes epideictic and deliberative dimensions through the strategic use of gratitude, moral appeals, democratic values, and religious expressions. The speech also reflects dominant elements of ethos and logos, particularly in constructing an image of political maturity, emotional stability, and ethical leadership. This study contributes to the development of political rhetoric studies in Indonesia by providing a contextual analysis of concession speeches as a form of post-electoral political communication within democratic processes